Animated Video in Teaching Reading Comprehension Viewed from the Students Reading Interest - Ani Sartika Sari (ELE Reviews: English Language Education Reviews, 2021)
The purposes of this study are to find out whether (1) animated video is effective in teaching reading comprehension, (2) students with high reading interest have better reading comprehension achievement than those with low reading interest, and (3) there is an interaction between the teaching media and the students reading interest in teaching reading comprehension. This study is experimental research. The population of this study is the students of MTs Negeri Prambanan. Two classes were taken as the sample, and the sampling technique used was cluster random sampling. This study applied tests and a questionnaire in collecting the data and Kolmogorov-Smirnov formula, One Way ANOVA, and multifactor analysis of variance in analyzing the data. Based on the result of data analysis, the research findings are: (1) animated video is effective in teaching reading comprehension of the students in MTs Negeri Prambanan (Fobtain = 7.60, Sig. Value < 0,05); (2) the students in MTs Negeri Prambanan with high reading interest have better reading comprehension achievement than those with low reading interest (Fobtain = 9.19, Sig. Value < 0,05); (3) there is an interaction between the teaching media and the students reading interest in teaching reading comprehension of the students in MTs Negeri Prambanan (Fobtain = 6.15, Sig. Value < 0,05). Based on these research findings, it can be concluded that animated video is effective in teaching reading comprehension of the students of MTs Negeri Prambanan. It brings improvement to the student's reading comprehension achievement.